Modernity and natalism in Russia: Historic perspectives - Nina Kouprianova (European Journal of Government and Economics (EJGE), 2013)
Less than desirable indigenous birth rates in Western Europe have generated interest toward examining the question of natalism - an organised state initiative to manage and promote reproduction, child rearing, health, as well as related neo-traditional cultural values - from a comparative perspective. This paper reviews the history of natalism in the USSR and contemporary Russia within the greater framework of modernity, by focusing on sweeping questions of ideology and geopolitics as well as current historic models. Economic stability is not an unimportant factor, yet it is authentic traditional culture that is of equal, if not greater, importance, even if expressed through state policies.
Keywords: 330; USSR; Russia; natalism; fertility; Modernity.